The Pilgrim Pope at the Time of the Contagion - Roberto Cipriani (Culture e Studi del Sociale)
The author tries to understand if the act performed in Rome, Sunday, March 15, 2020, by Pope Francis, who went on pilgrimage to the basilica of St. Mary Major to venerate Our Lady Salus populi romani and the church of St. Marcellus al Corso to pay homage to the Crucifix, is to be ascribed to the category of devotional or penitential pilgrimage. In communicative terms, what Pope Francis did in Rome is not an irrational, unconscious, impromptu action. Pope Bergoglio does not seem to put his person in the foreground. His constant conviction is to address everyone, without distinction of faith. His choice to go alone to St. Mary Major and St. Marcellus and his act of veneration of the Salus populi romani and the St. Marcellus Crucifix in St. Peter’s Square on March 27, 2020, respond to the same project of wide-ranging evangelization, which does not distinguish between believers and non-believers.